2018
DOI: 10.1111/1365-2664.13119
|View full text |Cite
|
Sign up to set email alerts
|

Crop rotation and agri‐environment schemes determine bumblebee communities via flower resources

Abstract: In many parts of the world, farmland pollinators decreased significantly during the last half of the 20th century mainly due to land‐use changes and agricultural intensification. We studied the effect of different typical crop rotations and agri‐environment schemes (AES) on bumblebee diversity in Estonia. We compared species abundances between four crop rotation types (cereal rollover [no change from 1 year to the next], cereal to mass‐flowering crops [hereafter MFC], MFC rollover and MFC to cereal fields) whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…; Marja et al . ). Therefore, effective AEM, which is targeted to enhance pollinator diversity, should be determined first of all by the availability of food resources.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…; Marja et al . ). Therefore, effective AEM, which is targeted to enhance pollinator diversity, should be determined first of all by the availability of food resources.…”
Section: Discussionmentioning
confidence: 97%
“…Our interaction model results indicated that large ecological contrast had in all cases (except when sample size was too small) significant positive effects on pollinator species richness. We determined in most cases ecological contrast by the difference between AEM and control sites in the amount of suitable flower resources providing energy and food for pollinators (Wood et al 2015;Marja et al 2018). Therefore, effective AEM, which is targeted to enhance pollinator diversity, should be determined first of all by the availability of food resources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Marja et al. ). Agroecological practices grounded in ecological theory have potential to minimize crop plant damage and enhance crop production through on‐farm management of habitat structure (Garibaldi et al.…”
Section: Introductionmentioning
confidence: 99%